Integrated Approach Methods in Teaching English in Music Education Lessons - Nazarova Sabrina Allaberdiyevna (Genius Journals, 2023)
This article presents scientific information about the methods of an integrated approach to teaching English in musical education classes
Keywords: musical education; integrated approach; method; English language